Hukum Perikatan dalam Transaksi Perbankan Syariah - Mahir Mahir (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2007)
This article emphasizes on contract law in islamic perspective. The important aspect about islamic economy is the aspect of transaction, in which contract is widely use in everyday economic activities. A transaction is an event in which a person commits to other person or in which two persons commits to implement a certain thing. From this event, a relationship appears between those two people. It is called a contract. A transaction creates a contract for people involved. Islamic banking in its operational puts forward values of islamic economy. It implies that islamic banking must complies on the implementation of norms of islamic law on contract. Before the amandment of the Law No.7/1989, the implementation of contract law in sharia financial institution referred to Civil Code which was basically translation of Burgerlijk Wetboek (BW), civil code of the Dutch Colonial authority since 1854. Consequently, the concept of islamic contract is not applicable. However, after the enactment of Law No. 3/2006 on the Revision of the Law No.7/1989 on Religious Court, the concept of islamic contract is applied and becomes the basis of business transaction of sharia financial institutions, especially islamic banking.